Effect of Maqashid Syariah Application on Corporate Governance in Sharia Hotels - Yuliafitri, Indri; Nurhayati, Euis; Amrania, Gia Kardina (Institut Agama Islam Negeri Kendari, 2020)
Indonesia is one of the countries with the largest Muslim population globally. This issue gives Indonesia has an excellent opportunity to develop the halal industry. Indonesia's halal industry is still inferior when compared to predominantly non-Muslim countries. Halal tourism, especially in this case sharia hotels, is one of the business lines that has received significant attention in this modern era. In recent years, tourism has become a different trend for various groups, leading to a demand for travel facilities that do not conflict with Islamic values. This study aimed to study the effect of the application of Maqashid Syariah on Corporate Governance in Sharia Hotels. The research methodology used is a survey. The type of data used in this study is primary data. Analysis of the data in this study was using simple regression analysis. The study results show that the implementation of Sharia Magashid has a significant influence on good governance and governance in sharia hotel management.